Contribution of strontium to the human diet from querns and millstones: an experiment in digestive strontium isotope uptake. (10th June 2019) - Johnson, L.; Montgomery, J.; Evans, J.; Hamilton, E.
Abstract : The question of whether rock grit ingested unintentionally from querns, metates or millstones, or deliberately through pica or geophagy, is bioaccessible in the human gut has not been addressed in archaeological strontium (Sr) isotope studies. This study employed the unified bioaccessibility method and determined that ingested rock grit can provide bioaccessible 87 Sr/ 86 Sr, but that unintentional consumption is unlikely to constitute > 1% of the diet (by mass) and will not significantly change, that is, by > 0.001, human skeletal 87 Sr/ 86 Sr. The use of locally or non‐locally sourced querns or millstones will not affect the interpretation of archaeological human 87 Sr/ 86 Sr values in Britain.